Comparing two maps by Geographer Robert de Vaugondy that represent the Kingdom of Portugal in the 18th century (1751) with the current mapping of the country as regards its topography, hydrography, shoreline definition and settlements - Neves dos Santos, Marco Pais (Geografares, 2014)
In our paper “Estudo de dois Mapas do Geografo Robert de Vaugondy relativos ao Reino de Portugal do Século XVIII (1751)” (Study on two maps by Geographer Robert de Vaugondy representing the Kingdom of Portugal in the 18th century), published in Revista Semina: Ciências Sociais e Humanas, Vol. 34, Issue No 1, 2013, we tried to give an explanation for the administrative divisions that appear in those maps. After having studied a number of texts dedicated to the period in question and other related documents, we came to the conclusion that the most logic explanation for those divisions is that they represent ecclesiastical divisions. In this paper, we go further in our analysis and compare these two maps with some current maps of Portugal, taking into account its topography, hydrography, shoreline definition and settlements. Although there are some errors in his maps, we can conclude that Robert de Vaugondy’s work, in terms of his knowledge and geographic representation of Portugal, was the best anyone could do at the time, and we restate the idea that the two maps represent ecclesiastical divisions.
Keywords: Robert de Vaugondy; Administrative Division; Geography of Portugal; Cartography